Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
John Seyman, Carmen Seyman, Cal Watkins, Jr., Laura Watkins, Jay Jory, Theresa Jory, Howard Sagaser, and Heidi Sagaser